The North Italian religious architecture and the riverside landscape of Alfredo Chaves, ES - Almonfrey, Juliana de Souza Silva (Farol, 2025)
This article presents a case study related to the development of religious architecture by Italian settlers in the riverside landscape of Espírito Santo. Through analysis, it reflects on the processes of assimilation and regional adaptation, as well as aspects of maintaining the traditions of the immigrants’ region of origin in the design of buildings. It understands architecture as a manifestation of the community’s identity and its formative moments.